Adaptability of Indian mustard (Brassica juncea) under irrigated uplands of Tripura - Chattopadhyay, K; Das, S P; Singh, N P (The Indian Journal of Agricultural Sciences, 2012)
Thirteen varieties of Indian mustard such as ‘Kranti’, PCR 7, Vardan, Sarama, Bio 902, Pusa Bahar, Vaibhav, Pusa Bold, Rohini, RH 30, PL 1359, Varuna and RH 819 were grown for consecutive three years to identify adaptable varieties for irrigated uplands of Tripura on the basis of yield contributing characters and seed yield. Based on correlation and path coefficient analysis, identified major traits like plant height, number of siliquae/plant, 1 000-seed weight along with seed yield were identified and were subjected to analysis of variances for stability using Freeman and Perkins stability analysis model. G × E interaction was linear for number of siliquae/plant, 1 000-seed weight and seed yield, suggesting their performance could be predicted. Based on stability parameters, varieties were identified for stable performance in component characters. Kranti with high mean value, near unity regression coefficient and non-significant deviation from regression in number of siliquae/plant, 1 000- seed weight and seed yield could be adapted for various environments. Varuna only was found suitable only for favourable environment while ‘Pusa Bold’ was identified for unfavourable condition.